Accessibility for everyone - Kalbag, Laura (Book Apart (Series), 2017)
You make the web more inclusive for everyone, everywhere, when you design with accessibility in mind. Let Laura Kalbag guide you through the accessibility landscape: understand disability and impairment challenges; get a handle on important laws and guidelines; and learn how to plan for, evaluate, and test accessible design. Leverage tools and techniques like clear copywriting, well-structured IA, meaningful HTML, and thoughtful design, to create a solid set of best practices. Whether you're new to the field or a seasoned pro, get sure footing on the path to designing with accessibility.